Selective in vitro transcription of one of the two Alu family repeats present in the 5' flanking region of the human epsilon-globin gene. - Di Segni, G (1981)
The sequence of 2965 nucleotides 5' of the human epsilon-globin gene has been completed. It includes two Alu family repeats present in an inverted configuration. Only the one located farthest from the gene was active as template for RNA polymerase III in a transcription system prepared from nuclei of Xenopus laevis oocytes. This selective transcription may be explained by the lack of homology of the first 45 nucleotides of the non transcribed repeat with other members of the Alu family. In fact this region includes one of the homology blocks described for other RNA polymerase III templates.